Impact of firm-level climate change exposure on firm value: The moderating role of carbon transparency - Shan Jin; Christopher Gan; Zhaohua Li (Borsa Istanbul Review)
This study uses a novel measure of climate change exposure at the firm level to investigate the impact of climate change on the value of Asia-Pacific non-financial firms. We examine whether increased carbon disclosure mitigates this impact. The findings reveal that a one-standard-deviation increase in climate change exposure reduces firm value by 4.14%, with this decline primarily driven by climate change-related opportunities and regulatory shock exposure. However, a higher level of carbon transparency significantly mitigates the negative effects of climate change exposure on firm value. Our heterogeneity analysis reveals that the moderating role of carbon transparency is more pronounced among firms operating in environments of lower institutional quality. These findings offer useful practical insights that can help policymakers and governance bodies design effective environmental disclosure regulations and robust institutional frameworks to reduce the adverse effects of climate change exposure on firm value.